WEWENANG POLISI DALAM MENEGAKKAN HUKUM - Tugimin Supriyadi; Intan Ratna Sari, Risma Ayu Sulistyowati, Suci Larosathy Putri, Talitha Fairuz Marsya Nugraha (ADMIN: Jurnal Administrasi Negara, 2024)
The authority of the police in law enforcement in Indonesia originates from Law Number 2 of 2002 concerning the Indonesian National Police. According to this law, the primary duties of the police are to maintain public security and order, enforce the law, and provide protection, guidance, and service to the community. The police are also granted the authority as investigators, which involves the process of identifying the perpetrators who violate the rights of suspects. The police are also tasked with the prevention and eradication of narcotics, as stated in Article 81 of Law Number 35 of 2009 concerning Narcotics. Additionally, the police have a duty to Hak Asasi Manusia (HAM). The authority of the police in law enforcement in Indonesia is part of a legal system that influences the fairness and orderliness of society. However, as mentioned in the work of R. Abdussalam, there are instances where the police take actions that do not align with the guidelines set by the law, which can violate other human rights.